If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12x + -3 = 4x Reorder the terms: -3 + 12x = 4x Solving -3 + 12x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -3 + 12x + -4x = 4x + -4x Combine like terms: 12x + -4x = 8x -3 + 8x = 4x + -4x Combine like terms: 4x + -4x = 0 -3 + 8x = 0 Add '3' to each side of the equation. -3 + 3 + 8x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + 8x = 0 + 3 8x = 0 + 3 Combine like terms: 0 + 3 = 3 8x = 3 Divide each side by '8'. x = 0.375 Simplifying x = 0.375
| 3(x-2)-4=4x-2 | | 9y=2y+35 | | v^2-2=65 | | 2y+1=23 | | 12k-32=24 | | -n+1-7n=9-7n | | -3+6x=x+7 | | z+3.6=2.5 | | -0.24p+1.602=1.29 | | 1X+4Y=58 | | -5x-10=-3+2x | | 7(n-4)-(6-3n)=9n | | 0,001*0,001x=1/8 | | 2+3x=-5x-6 | | 2x-5=-2+x | | H=0.001x^2-X+27 | | 12h=72 | | (x+4)+(x+2)+(x+5)=2(x+1)+2(x+3) | | 90m^2+21mn-6n^2=0 | | T-75H=735 | | 9x+7-7x=4+x+5 | | -2=6+2x | | -20=b-5 | | 8-n=6+4n | | -9+7m=1+5m | | (m+2)(m-2)=0 | | 3(5-q)+6=9 | | 5(x+2)-(2x-7)= | | 10g=1100 | | x+4+x+2+x+5=2(x+1)+2(x+3) | | 10=1100 | | 3x-6=-14-7+6x+6 |